Indonesian Honey Consumers' Behavior and Sensory Preference for Commercial Trigona Honey - Melina Melina; Dede Robiatul Adawiyah; Dase Hunaefi (Jurnal Teknologi dan Industri Pangan, 2023)
Consumption of honey has increased in recent years. This included trigona honey as a new market that is developing. This research was conducted to (1) identify the consumption patterns for Indonesian honey, and (2) identify the sensory attributes of honey considered ideal by consumers which influence consumer acceptance and satisfaction. There were 2 stages of activity in this study, including a consumption online survey by 225 respondents and a sensory testing of honey samples using the CATA (check-all-that-apply) method involving 64 untrained panelists. Data analysis was carried out using SPSS and XLSTAT 2022 software. There were 4 honey samples used in this study: 2 Apis bee honey samples and 2 trigona honey samples. The study showed that the consumption pattern of Indonesian honey consumers is influenced by the consumers’ age and income. Health benefits, brand awareness, and taste of honey were the important factors in consumer behavior. Apis bee honeys were perceived as the ideal honey by consumers as they were very familiar with the taste. The sweet aroma, sweet aftertaste, caramel flavor, and viscous attributes of Apis bee honey were the attributes that the consumers like. The floral flavor and fruity aroma found in trigona honey were appealing. However, the strong sour aroma, taste, and aftertaste found in trigona honeys decrease the Indonesian consumers liking.